The Effect of Public Policy on the Spatial Distribution of Orange County's Homeless Population| A Case Study in the Lower Santa Ana River Area - Shaw, William Timothy (California State University, Long Beach, 2018)
The whereabouts of the unsheltered homeless population in Orange County, CA is determined by various push-pull factors. Access to services, methods and intensity of policing, and general tolerance by local residents or business owners all factor into where those experiencing homelessness will congregate. Public policy is related to these concepts as it is influenced by resident input and is the tool used to implement services and guide law enforcement. This thesis takes a closer look into factors specific to the rapid growth of homeless encampments at the Santa Ana Riverbed in Northern Orange County. The research tracks the growth of homeless encampments in the study area dating back to 2013 using geospatial techniques and analyzes the increase in numbers in relation to changes in local policies, such as anti-camping ordinances. Specifically, the research relied upon analysis of aerial imagery and data collected in the field. The study finds that disproportionate enforcement of anti-camping laws in the riverbed and adjacent cities created a hospitable area for homeless persons in the Santa Ana Riverbed. Finding a catalyst that explains the rapid growth of encampments in the last two years is less clear, but likely due to a variety of factors.